MENINGKATKAN KEMAMPUAN BANTU DIRI ANAK AUTISTIK MELALUI METODE INTERVENSI DAN TINGKAT KECERDASAN - Karsih Karsih (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2012)
The objective of this research was to investigate the effect of intervention method and intelligence level on the improvement of autistic children’s self-help skills. This experimental research was conducted at TLPA Pelita Hati, Jakarta as from September through December 2010 involving 12 samples with different intelligence levels from the total population of 24 children. Employing Analysis of Variance (ANOVA) and t-test toward four null hypotheses, the results of the study indicate that: (a) the improvement of self help skills of autistic children given Visual Method is more significant than those with the Lovaas Method, (b) the autistic children of high intelligence get better intervention by Visual Method than the Lovaas Method, (c) the autistic children of low intelligence get better intervention by Lovaas Method, and (d) there is an interaction effect of intervention method and intelligence level on the improvement of autistic children’s self-help skills. The findings are expected to be beneficial to autistic therapist, teachers, parents, and special educational managers